The Use of the Esclera Scleral Contact Lens in the Treatment of Moderate to Severe Dry Eye Disease - La Porta Weber, Sarah; Becco de Souza, Rodrigo; Gomes, José Álvaro Pereira; Hofling-Lima, Ana Luisa (American journal of ophthalmology, 2016)
To evaluate the efficacy of the Esclera scleral contact lens (SCL) treatment and its impact on clinical testing for moderate to severe dry eye disease (DED). Prospective interventional case series. A total of 41 eyes from 25 patients with moderate to severe DED were evaluated for the Esclera SCL treatment. Best-corrected visual acuity (BCVA), tear osmolarity, the Schirmer I test, tear film breakup time (TBUT), corneal and conjunctival staining, meibomian grading, and Ocular Surface Disease Index and SF-36v2 questionnaires were assessed before and after the SCL treatment. These values were compared to assess the real benefit of using SCL as a treatment for DED. Forty-one eyes from 25 patients were fitted with SCL for management of DED. The underlying diseases were Stevens-Johnson syndrome (22 eyes), Sjogren syndrome (11 eyes), graft-vs-host disease (2 eyes), dry eye after keratomileusis in situ (2 eyes), and undifferentiated ocular surface disease (4 eyes). BCVA improved from 0.703 ± 0.55 logMAR with habitual correction to 0.406 ± 0.43 logMAR with SCL (P < .001). There was a significant decrease in tear osmolarity values (338.1 ± 27.1 to 314.25 ± 38.8 mOsm/L, P < .001) and van Bijsterveld scores (3.63 ± 2.33 to 2.63 ± 2.46 grade, P = .015) between the baseline and 12 months after SCL wear. There were also significant improvements in dry eye symptoms and quality of life as assessed by the OSDI and SF-36v2 questionnaires (both with P < .001). The Esclera SCL treatment had a positive impact on tear osmolarity and van Bijsterveld score, as well as an improvement in the patients' BCVA, dry eye symptoms, and quality of life.